1992
DOI: 10.1038/clpt.1992.171
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of cyclosporine with concomitant rifampin administration is markedly less than predicted by hepatic enzyme induction

Abstract: The pharmacokinetics of cyclosporine was studied in six healthy volunteers after administration of the drug orally (10 mg/kg) and intravenously (3 mg/kg) with and without concomitant rifampin administration. Both blood and plasma (separated at 37 degrees C) samples were analyzed for cyclosporine concentration. For blood and plasma, respectively, clearances of cyclosporine were calculated to be 0.30 and 0.55 L/hr/kg, values for volume of distribution at steady state were 1.31 and 1.68 L/kg, and bioavailabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
165
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(172 citation statements)
references
References 0 publications
6
165
1
Order By: Relevance
“…The increased elimination of quinine in subjects receiving rifampicin is consistent with induction of CYP3A-mediated metabolism. Similar findings have been reported for quinidine [9], and cyclosporine [8], also metabolised by CYP3A.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The increased elimination of quinine in subjects receiving rifampicin is consistent with induction of CYP3A-mediated metabolism. Similar findings have been reported for quinidine [9], and cyclosporine [8], also metabolised by CYP3A.…”
Section: Discussionsupporting
confidence: 77%
“…Quinine is widely used to treat malaria in endemic phylline, antipyrine, hexobarbitone and cyclosporine malaria areas where Plasmodium falciparum is resist- [2][3][4][5][6][7][8]. It has been shown that rifampicin decreases the ant to chloroquine.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, CYP3A accounts for about 30 and 70% of total CYP activity in the liver and small intestine, respectively [12][13][14], and intestinal first-pass metabolism mediated by CYP3A has been shown to be clinically relevant for several drugs, including cyclosporin A [15,16]. However, it remains to be fully clarified whether P-gp and/or CYP3A controls the oral bioavailability of cyclosporin A by limiting absorption from the small intestine.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Again in such studies extent than would be predicted from the increase in it is essential that both qualitative and quantitative hepatic metabolism; this is due to an additional aspects of induction are considered. induction of intestinal P450 enzymes that appears greater than the induction of hepatic metabolism [70 ].…”
Section: Mechanism Of Enzyme Inductionmentioning
confidence: 99%